Digital Accounting Systems (DIS): Concepts, Components and Roles in Business - Hong Nhung Dao Thi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Today, with the continuous development of science and technology, the most advanced technology has been applied to the field of human activities, from production and business to monitoring and management. Technology helps people manage work more efficiently and quickly, while providing timely and reliable information. Accounting is a leading important part of the economic and financial management system, playing a great role in controlling, managing and operating the production and business activities of enterprises, especially in the financial sector. current period. That requires businesses to apply technology to the organization that performs accounting work with the aim of creating an effective accounting information system. Such system must be reasonable, rigorous, provide truthful, timely and reliable information with the most advanced processing techniques. That not only contributes to increasing competitiveness but also improves operational efficiency in enterprises. This is an inevitable development trend and is consistent with the renovation process, especially in the current period of economic integration. In this article, Research on the concept of a digital accounting information system and a plan to develop an accounting information system in an enterprise.